The role of the dorsal raphé nucleus in reward-seeking behavior - Nakamura, Kae (Frontiers in Integrative Neuroscience, 2013)
Pharmacological experiments have shown that the modulation of brain serotonin levels has a strong impact on value-based decision making. Anatomical and physiological evidence also revealed that the dorsal raphé nucleus (DRN), a major source of serotonin, and the dopamine system receive common inputs from brain regions associated with appetitive and aversive information processing. The serotonin and dopamine systems also have reciprocal functional influences on each other. However, the specific mechanism by which serotonin affects value-based decision making is not clear. To understand the information carried by the DRN for reward-seeking behavior, we measured single neuron activity in the primate DRN during the performance of saccade tasks to obtain different amounts of a reward. We found that DRN neuronal activity was characterized by tonic modulation that was altered by the expected and received reward value. Consistent reward-dependent modulation across different task periods suggested that DRN activity kept track of the reward value throughout a trial. The DRN was also characterized by modulation of its activity in the opposite direction by different neuronal subgroups, one firing strongly for the prediction and receipt of large rewards, with the other firing strongly for small rewards. Conversely, putative dopamine neurons showed positive phasic responses to reward-indicating cues and the receipt of an unexpected reward amount, which supports the reward prediction error signal hypothesis of dopamine. I suggest that the tonic reward monitoring signal of the DRN, possibly together with its interaction with the dopamine system, reports a continuous level of motivation throughout the performance of a task. Such a signal may provide “reward context” information to the targets of DRN projections, where it may be integrated further with incoming motivationally salient information.